THE EFFECTIVENESS OF SERVICE QUALITY AND ACADEMIC SYSTEM INFORMATION TOWARD THE SATISFACTION AND LOYALTY OF STUDENT ( RESEARCH AT HARAPAN BANGSA PURWOKERTO INSTITUTE OF HEALTH SCIENCES ) - Indrawati, Iin Dyah (STIE AUB Surakarta)
The purpose of this study was to find out the influences of service quality dimensions such as tangibles, reliability, responsiveness, assurance, empathy and Academic System Information to satisfaction and the influences of all variables to loyalty of students at Harapan Bangsa Purwokerto institute of health sciences. The used technique sampling in this study was random sampling method. The sample in this research was 128 respondents. The data collecting techniques is used observation and questionnaires. The data analytical technique used research instrument test such as validity and reliability tests, linearity test, hypothesis tests such as path analysis, t test, F test, determination coefficient, and coefficient correlation of variables. The test results showed that all instruments were valid and reliable. The analysis results of this study shown that: tangible, reliability, and assurance had a positive and significant effect to satisfaction, responsiveness and Academic Information System had a positive but insignificant effect to satisfaction. Empathy had a negative and insignificant effect to satisfaction. Tangibles, reliability, empathy and satisfaction had a positive and significant effect to loyalty, responsiveness and satisfaction had a positive but insignificant effect to loyalty, and assurance and Academic Information System had a negative and insignificant effect to loyalty. Tangibles, reliability, responsiveness, assurance, empathy, trust and satisfaction simultaneously had a significant effect to loyalty. The results of path analysis showed that: the direct effect of tangibles to loyalty was more effective rather than the indirect effect via satisfaction. The indirect effect of reliability to loyalty via satisfaction was more effective rather than the direct effect to loyalty. The direct effect of responsiveness to loyalty was more effective rather than the indirect effect via satisfaction. The indirect effect of assurance to loyalty via satisfaction was more effective rather than the direct effect to loyalty. The direct effect of empathy to loyalty was more effective rather than the indirect effect via satisfaction. The indirect effect of Academic Information System to loyalty via satisfaction was more effective rather than the direct effect to loyalty. The indirect effect of satisfaction as variable of intervening in this study was able to mediate variable of reliability, assurance and Academic Information System to loyalty but it was unable to mediate variable of tangibles, responsiveness and empathy to loyalty. Tangible was the most dominant variable effect to loyalty. The total effect of tangible to loyalty via satisfaction was most dominant total effect to loyaltyKeywords: Service quality dimensions, Academic Information System, satisfaction, and loyalty.